Pengembangan Paradigma Wasathiyah dalam Ilmu Ekonomi Islam - fathurrahman, Ayif (Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2025)
This article aims to discuss the development of the wasathiyah paradigm in Islamic economics. The approach in this study is a qualitative approach. This study was designed in the form of library research using various library sources as sources of research data. The results of the study are that the wasathiyah paradigm in Islamic economics is the original paradigm of Islamic economics because it originates from the Qur'an which is intended as a guideline for humans in carrying out economic activities. There are 3 dimensions of wasathiyah that are very likely to be applied as a basis for the development of Islamic economics, first, the wasathan dimension (middle) to avoid the extremism of economic thinking that has occurred in the capitalist economic system and the socialist economic system. Second, the dimension of progress as the best economic model to realize human welfare. Third, the worldly-ukhrowi dimension, the unificative dimension between the world and the hereafter which gave birth to the concept of falah as the goal of Islamic economics, the pursuit of worldly material means can be maximized in order to maximize the implementation of worship to Allah SWT to be more perfect.